2019
DOI: 10.1111/jth.14477
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent venous thromboembolism after acute pulmonary embolism: Role of residual pulmonary obstruction and persistent right ventricular dysfunction. A meta‐analysis

Abstract: Debated is the role of residual pulmonary obstruction (RPO) in predicting venous thromboembolism. Whether right ventricular dysfunction (RVD) predicts recurrent venous thromboembolism is unknown. 15 studies on RPO and 4 on RVD and venous thromboembolism were included in this meta‐analysis. RPO is a predictor of recurrent venous thromboembolism when assessed by perfusion lung scan. RVD after acute pulmonary embolism is not associated with recurrent venous thromboembolism. Background There is conflicting evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 49 publications
1
16
0
1
Order By: Relevance
“…In a recent meta-analysis, a twofold increased risk of recurrent VTE was observed in patients with RPVO. 21 In post hoc analysis of the PADIS-PE trial, we also found that PVOI measured at PE diagnosis was correlated with RPVO. 13,22 Since initial PVOI is easily measurable at PE diagnosis, our finding suggests that clinicians could use initial PVOI measurement instead of RPVO, and so spare patients one additional V/Q scan.…”
Section: Pulmonary Vascular Obstruction and Pulmonary Embolism Orionementioning
confidence: 56%
“…In a recent meta-analysis, a twofold increased risk of recurrent VTE was observed in patients with RPVO. 21 In post hoc analysis of the PADIS-PE trial, we also found that PVOI measured at PE diagnosis was correlated with RPVO. 13,22 Since initial PVOI is easily measurable at PE diagnosis, our finding suggests that clinicians could use initial PVOI measurement instead of RPVO, and so spare patients one additional V/Q scan.…”
Section: Pulmonary Vascular Obstruction and Pulmonary Embolism Orionementioning
confidence: 56%
“…Risk stratification for patients with unprovoked venous thromboembolism may also help to determine the risk of recurrent thrombosis. Prognostic markers of recurrent venous thromboembolism include male sex, advanced age,137138 inherited thrombophilia,70 obesity,70 persistently positive D-dimer,77139 and residual pulmonary obstruction on ventilation-perfusion lung scan 140. Individually, these risk factors are insufficient to recommend long term anticoagulation; however, risk prediction models incorporating various combinations have been proposed 137138.…”
Section: Duration Of Treatment For Pulmonary Embolismmentioning
confidence: 99%
“…The rate of RPO following an acute PE appears to depend on the size of the initial clot burden and is reported to be as high as 60% [26,27]. Many studies have now evaluated the utility of RPO in predicting recurrent PE in patients with an acute PE treated with at least three months of oral anticoagulation.…”
Section: Residual Pulmonary Obstructionmentioning
confidence: 99%
“…Pesavento et al showed that, in patients with RPO, 25/324 (7.7%) developed recurrent VTE versus 15/323 (4.6%) in patients without RPO, and RPO was found to be an independent predictor of both VTE recurrence and CTEPH (hazard ratio (HR) 2.26, 95% confidence interval (CI) 1.23-4.16, p = 0.009) [29]. Furthermore, a recent meta-analysis evaluating RPO and recurrent VTE determined that RPO was associated with an increased risk of recurrent VTE detected by VQ scan (odds ratio (OR) 2.22, 95% CI 1.61-3.05) [26]. These findings demonstrate that RPO detection following acute PE may increase the risk of recurrent VTE, but as the overall rate of recurrence in this cohort remains relatively low, its utility in predicting the likelihood of recurrent events is minimal, and it should not be used primarily for this purpose.…”
Section: Residual Pulmonary Obstructionmentioning
confidence: 99%